The fractal dimension behaviour of the domain patterns in ferrite-garnet films - A.D. Zigert; G.G. Dunaeva; N.B. Kuz`min; E.M. Semenova; N.Yu. Sdobnyakov (Физико-химические аспекты изучения кластеров, наноструктур и наноматериалов, 2023)
In this work, using a set of experimental techniques and specialized software, we studied bismuth-containing ferrite garnet films of various thicknesses and with different stoichiometric compositions grown on gadolinium gallium garnet substrates. The limiting magnetic hysteresis loops for defective and defect-free sections of films were obtained using the optical magnetometry method. The field dependences of the fractal dimension of magneto-optical images were also obtained. For various compositions and thicknesses of bismuth-containing ferrite-garnet films, ranges of changes in the fractal dimension were obtained. The fractal dimension was determined by the counting cube method. The mutual behavior of the field dependences of the fractal dimension and the first derivative of magnetization with respect to the field dM(H)/dH is analyzed. The characteristic features of the behavior of the first derivative of magnetization with respect to the field dM(H)/dH with a change in the film thickness, as well as for defective and defect-free sections of films, have been established.